On the evidence for human use and control of fire at Schöningen. Issue 89 (December 2015) - Stahlschmidt, Mareike C.; Miller, Christopher E.; Ligouis, Bertrand; Hambach, Ulrich; Goldberg, Paul; Berna, Francesco; Richter, Daniel; Urban, Brigitte; Serangeli, Jordi; Conard, Nicholas J.
Abstract: When and how humans began to control fire has been a central debate in Paleolithic archaeology for decades. Fire plays an important role in technology, social organization, subsistence, and manipulation of the environment and is widely seen as a necessary adaptation for the colonization of northern latitudes. Many researchers view purported hearths, burnt wooden implements, and heated flints from Schöningen as providing the best evidence for the control of fire in the Lower Paleolithic of Northern Europe. Here we present results of a multianalytical study of the purported hearths along with a critical examination of other possible evidence of human use or control of fire at Schöningen. We conclude that the analyzed features and artifacts present no convincing evidence for human use or control of fire. Our study also shows that a multianalytical, micro-contextual approach is the best methodology for evaluating claims of early evidence of human-controlled fire. We advise caution with macroscopic, qualitative identification of combustion features, burnt flint, and burnt wood without the application of such techniques as micromorphology, Fourier transform infrared (FTIR) spectroscopy, organic petrology, luminescence, and analysis of mineral magnetic parameters. The lack of evidence for the human control of fire at Schöningen raises the possibility that fire control was not a necessary adaptation for the human settlement of northern latitudes in the Lower Paleolithic.